2011
DOI: 10.1007/s11116-011-9336-y
|View full text |Cite
|
Sign up to set email alerts
|

Importance of traveler attitudes in the choice of public transportation to work: findings from the Regional Transportation Authority Attitudinal Survey

Abstract: Mode choice, Public transportation, Attitudes and perceptions, Factor analysis, Logistic regression, Elasticities,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 10 publications
3
27
1
Order By: Relevance
“…The willingness to use a mode and the loyalty to the mode are important attitudinal constructs uncovered by the analysis presented in this research, a finding supported by Shiftan et al (2008) and Shiftan et al (2015). Lieberman et al (2001) and Popuri et al (2011) also found concern for the comfort and the perceived safety in the level of service of public transport.…”
Section: Cit2016 -Xii Congreso De Ingeniería Del Transportesupporting
confidence: 52%
“…The willingness to use a mode and the loyalty to the mode are important attitudinal constructs uncovered by the analysis presented in this research, a finding supported by Shiftan et al (2008) and Shiftan et al (2015). Lieberman et al (2001) and Popuri et al (2011) also found concern for the comfort and the perceived safety in the level of service of public transport.…”
Section: Cit2016 -Xii Congreso De Ingeniería Del Transportesupporting
confidence: 52%
“…Public transport very often means crowds and standing in the vehicle, so it is no wonder that if there is a possibility of choice, this transport mode is less interesting for older adults and the elderly [23]. Besides convenience, some studies showed that attitudes towards transport mode use [24] as well as social status-related attitudes are predictors of transport mode preferences [25], which could also explain the strong car-only use habit among older adults and elderly people in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since Lebanon does not have trains, metros, or somewhat acceptable bus transport system, travelers call for taxi service or utilize a car for hire service rather than flagging down passing cabs. "Since attitudes toward travel affect the daily mode choice behavior, the choice of public transportation could in turn affect attitudes in the longer term" (Popuri, Proussaloglou, Ayvalik, Koppelman, & Lee, 2011).…”
Section: Safety Of Public Transportmentioning
confidence: 99%